Evidence for a 10-year TBE vaccine booster interval: an evaluation of current data - Jörg Schelling; Suzanne Einmahl; Ralph Torgler; Carsten Schade Larsen (Expert Review of Vaccines)
Introduction Tick-borne encephalitis (TBE) is rapidly spreading to new areas in many parts of Europe. While vaccination remains the most effective method of protection against the disease, vaccine uptake is low in many endemic countries.Areas covered We conducted a literature search of the MEDLINE database to identify articles published from 2018 to 2023 that evaluated the immunogenicity and effectiveness of TBE vaccines, particularly Encepur, when booster doses were administered up to 10 years apart. We searched PubMed with the MeSH terms ‘Encephalitis, Tick-Borne/prevention and control’ and ‘Vaccination’ for articles published in the English language.Expert opinion Long-term immunogenicity data for Encepur and real-world data on vaccine effectiveness and breakthrough infections following the two European TBE vaccines, Encepur and FSME-Immun, have shown that extending the booster interval from 3–5 years to 10 years does not negatively impact protection against TBE, regardless of age. Such extension not only streamlines the vaccination schedules but may also increase vaccine uptake and compliance among those living in endemic regions.